2017
DOI: 10.1097/coc.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

Meningioma in Breast Cancer Patients

Abstract: Women with BC and meningioma have smaller-sized meningiomas and more advanced BCs compared with women having only 1 diagnosis. As there was no temporal relationship between size and latency between tumor diagnoses, the disparity in meningioma size between BC-meningioma and meningioma cohorts may have BC-associated biological components that warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
0
18
1
Order By: Relevance
“…Furthermore, grade of meningiomas cannot be differentiated from NHIRD, and it hinders us to assess if tamoxifen use or not has different effects on different grades of meningioma. Milano et al found that women with both breast cancer and meningioma tended to have more advanced breast cancers and smaller-sized meningiomas compared with women having only one of these diagnoses (Milano and Grossman, 2017); unfortunately, the current study cannot justify it. Second, precise brain MRI and CT information is unavailable in the NHIRD, and the resulting potential surveillance bias precludes a fair comparison of the risk of meningioma in breast cancer patients with that in the normal population.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Furthermore, grade of meningiomas cannot be differentiated from NHIRD, and it hinders us to assess if tamoxifen use or not has different effects on different grades of meningioma. Milano et al found that women with both breast cancer and meningioma tended to have more advanced breast cancers and smaller-sized meningiomas compared with women having only one of these diagnoses (Milano and Grossman, 2017); unfortunately, the current study cannot justify it. Second, precise brain MRI and CT information is unavailable in the NHIRD, and the resulting potential surveillance bias precludes a fair comparison of the risk of meningioma in breast cancer patients with that in the normal population.…”
Section: Discussioncontrasting
confidence: 69%
“…The breast cancer–meningioma relationship has been investigated for decades, but the results have been discordant. Several studies have detected a positive association between these two conditions (Schoenberg et al, 1975; Helseth et al, 1989; Lieu et al, 2003; Rakha et al, 2007; Rao et al, 2009; Milano and Grossman, 2017). For example, Rao et al found a strong association between breast cancer and meningioma, but only in women (Rao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher incidence of meningiomas among women with previous breast cancer seems to be a fact, since recent papers identi ed a 26% higher meningioma incidence in this population 7 . Due to the reported link between BC and female hormones and also between meningioma and these hormones, it has been hypothesized that meningiomas and BCs may be linked 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason for this correlation in incidence is suspected to be the usage of cranial imaging for staging and/ or follow-up, particularly among women with more advanced breast cancer. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%